Ichthyodiversity of the Bangshi river, Savar, Dhaka (Jahangirnagar University Journal of Biological Sciences, 2016)
Fish diversity of Bangshi river, Savar, Dhaka was studied over a period of two consecutive years (July, 2010 to June, 2012). A total of 48 fish species belonging to 39 genera, 18 families and 8 orders were recorded. Siluriformes was the most dominant order comprising 33.33% of all the number of species recorded, followed by the Cypriniformes (31.25%), Perciformes (14.58%), Clupiformes (6.25%), Channiformes (6.25%), Osteoglossiformes (4.16%), Synbranchiformes (2.08%) and Beloniformes (2.08%). The most dominated species of this study were Ailia punctata, Mystus tengra and Puntius sophore and rare species was Bagarius yarrellii. During the study 29 sp. (40.42%) fish species were found to be locally rare, whereas, only 3sp. (6.25% ) were very common and 16 sp. (33.33%) were common in occurrence. Among the fishes, 52.08% was threatened in which vulnerable, endangered and critically endangered were 20%, 36% and 44% respectively.Jahangirnagar University J. Biol. Sci. 4(1): 19-25, 2015 (June)